Do bone mineral content and density determine fracture in children? A possible threshold for physical activity - Martins, A (2017)
Background: Relations between bone parameters, physical exertion, and childhood fractures are complex. We aimed to estimate the associations between fracture history and bone mineral content (BMC) and areal bone mineral density (aBMD) at 7 years of age, by levels of physical activity, as a proxy for trauma frequency. Methods: We used data collected from 2,261 children of the Generation XXI birth cohort, assembled in 2005/6 in Porto, Portugal. At the age of 7 years (2012/4), fracture history, time spent per week in active play, and sports practice were reported by parents. Subtotal and lumbar spine (LS) BMC and aBMD were measured using whole-body dual-energy X-ray absorptiometry. Results: Boys and girls in the highest categories of time spent in sports practice or active play generally had higher BMC and aBMD. Among girls, BMC and aBMD were protective of fracture only in the highest quarter of active play (>660 min/week)—odds ratios (OR; 95% confidence interval (95% CI)) for subtotal BMC=0.27 (0.11–0.67), subtotal aBMD=0.18 (0.06–0.49), and LS aBMD=0.41 (0.22–0.75). For boys in the highest quarter of sports practice (>240 min/week), subtotal and LS BMC were protective of fracture—OR=0.39 (0.16–0.98) and 0.51 (0.27–0.96), respectively. Conclusion: In prepubertal children, BMC and aBMD predicted fracture history only in the highest levels of physical activity.